Developing of Drama Teaching Materials with Benime Assisted for High School Students - Trisnawati Hutagalung; Dwi Friska Br. Girsang; Novhira Putri Paino (Indonesia Approach Education, 2023)
This research and development is to find out the product development process and feasibility, as well as to find out the effectiveness of the drama material development product using the Benime application for class XI students at SMA Negeri 1 Hamparan Perak. The process of developing drama material uses the Benime application in the form of audiovisual teaching materials using the stages of the R&D method by Borg and Gall with 8 research stages covering 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) small-scale trials, 7) product revisions, and 8) mass production. From the validation results obtained a score calculation from material experts of 82% very good